Bangladesh - Beyond Connections : Energy Access Diagnostic Report Based on the Multi-Tier Framework - Samad, Hussain A. (World Bank, Washington, DC, 2021)
The Energy Sector Management Assistance Program (ESMAP) in the World Bank, in consultation with multiple development partners, has developed the Multi-Tier Framework (MTF) to measure and monitor energy access in terms of attributes and tiers. The MTF defines energy access as one that is adequate, available when needed, reliable, of good quality, affordable, legal, convenient, healthy, and safe for all required energy applications across households, productive enterprises, and community institutions. As part of the stock-taking exercise on measuring access using MTF, ESMAP has launched detailed data collection activities in seventeen countries, including Bangladesh. Findings of this report are based on nationally representative data on access to electricity and cooking solutions.